From the Rise and Fall of Quantum Radar to Proposed Improvements of Research Assessment - Galati, Gaspare; Pavan, Gabriele; Daum, Frederick (Technium Social Sciences Journal, 2026)
It appears that many researchers and scientific journalists wish to ignore the Chinese proverb “If what you say doesn’t improve the silence, don’t say it”. Hence, it is more and more difficult to distinguish the constructive and reliable results and methodologies of scientific and technological research from a lot of useless, misleading and deceptive content within a vast and growing sea of information. In the publications world, this very critical situation is coped with the predatory eco-system to which most researchers are subjected and with the damaging effects of the widespread misuse of bibliometric indexes. Our analysis starts from the particular research area of radar theory and techniques, well known to us. Through a generalization process, the exemplary case of Quantum Radar (QR) allows us to study in detail the effects of the aforementioned general situation on the research and development, on the assessment procedures and on the evaluation of results. Our conceptual contribution to research assessment and evaluation is resumed as follows. (a) At least a case of important failure of research assessment is demonstrated “beyond reasonable doubt”. Therefore, one may logically deduce that many other do exist. (b) Publications show an increasing quantity coped with a decreasing quality. (c) The assessment based on bibliometric indexes is a more and more critical process; the same applies to the assessment based on peer review. Hence, effective evaluation strategies are needed. The main conclusion of our analysis is that the present situation – and its trends – call for new research assessment and evaluation procedures at the international level. In this frame, (im)possible proposals, which include the regulations of scientific publications and a related international agency, are presented. Keywords.